Study of the influence of psychological mood on the performance and mental health of athletes in VR-aided basketball training - Wang, Haiyan (Frontiers in Psychology, 2024)
The purpose of this study is to determine the influence of psychological mood on the performance and mental health of athletes during VR training. The study involved representatives of both men's and women's basketball teams from universities in China (62 girls and 65 boys, whose average age was 18.2). The participants were divided into 2 groups. Both groups trained regularly, except the experimental group used VR technology, while the control group did not. To study the physical performance of respondents, a complex psychophysiological test was used. The Warwick-Edinburgh Mental Well-Being Scale (WEMWBS) was used to assess the psychological mood and mental health of respondents. The VR training has been proven to increase the psychological attitude of basketball players during the training. Specifically, it has a positive effect on the psychophysiological performance indicators and mental health of athletes. Prospective research will be aimed at a comparative study of the impact of VR technology in the training process on the results of basketball players and representatives of other team sports